Review of Islamic Law on E-Commerce Buying and Selling Transactions - Siagian, Adelini Siagian (Universitas Islam Negeri Sumatera Utara, 2021)
Now transaction activities due to rapid technological developments have shown anew face. The trend of buying and selling via online media, aka e-commerce, is nowspreading like mushrooms in the rainy season. Globally, perpetrators of these methods, both as sellers and buyers, also involve Muslims. To provide a legal basis for this reality, fiqhiyah studies must be built as a normative and practical basis for those who wish to carry out transactions. The basic concept of e-commerce, namely purchasing goods, has been known and practiced since the early generations of Islam, known as as-Salam. So this research will include descriptive analysis regarding the correlation of these two concepts. Ecommerce and as-salam have many similaritiesand also significant differences. One of the differences is the legal basis used in the two concepts. Othe differences, such as the way of offering, or the way of making transactions, the way of delivery and acceptance. Technical differences that exist. As part of a direct agreement between buyers and sellers, a product and service catalog will be provided, so that buyers can obtain complete information. The purpose of writing this research is to determine the legal relationship between buying and selling e-commerce and as-salam. The data and information obtained at the data collection stage are then processed using descriptive analysis methods based on secondary data.